Association of Medical Financial Hardship and Mortality Among Cancer Survivors in the United States. (20th April 2022) - Yabroff, K Robin; Han, Xuesong; Song, Weishan; Zhao, Jingxuan; Nogueira, Leticia; Pollack, Craig E; Jemal, Ahmedin; Zheng, Zhiyuan
Abstract: Background: Cancer survivors frequently experience medical financial hardship in the United States. Little is known, however, about long-term health consequences. This study examines the associations of financial hardship and mortality in a large nationally representative sample of cancer survivors. Methods: We identified cancer survivors aged 18-64 years (n = 14 917) and 65-79 years (n = 10 391) from the 1997-2014 National Health Interview Survey and its linked mortality files with vital status through December 31, 2015. Medical financial hardship was measured as problems affording care or delaying or forgoing any care because of cost in the past 12 months. Risk of mortality was estimated with separate weighted Cox proportional hazards models by age group with age as the timescale, controlling for the effects of sociodemographic characteristics. Health insurance coverage was added sequentially to multivariable models. Results: Among cancer survivors aged 18-64 years and 65-79 years, 29.6% and 11.0%, respectively, reported financial hardship in the past 12 months. Survivors with hardship had higher adjusted mortality risk than their counterparts in both age groups: 18-64 years (hazard ratio [HR] = 1.17, 95% confidence interval [CI] = 1.04 to 1.30) and 65-79 years (HR = 1.14, 95% CI = 1.02 to 1.28). Further adjustment for health insurance reduced the magnitude of association of hardship and mortality among survivors aged 18-64 years (HR = 1.09, 95% CI = 0.97 to 1.24). Adjustment for supplemental Medicare coverage had little effect among survivors aged 65-79 years (HR = 1.15, 95% CI = 1.02 to 1.29). Conclusion: Medical financial hardship was associated with mortality risk among cancer survivors in the United States.